FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DALAM MENGAWASI KINERJA KEPALA DESA DI DESA KUOK KECAMATAN KUOK KABUPATEN KAMPAR - Elpita Heriyanti; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
One of bpd’s function is implementation control of performance from head village. In the case, bpd required to execute a function with either and true that the governments in the village can’t abuse their authority and predefined rules. The goals of this research to know function of BPD in monitoring the performance of head village is going well or not. This research was conducted in the village of Kuok, District Kampar.This research using theorist from Manullang about standard monitoring an activity in orgtanization. Informans research are head of BPD, Head village and comunity of Kuok village. Data collection techniques used are observation, interview, and documentation. While the types and sources of data are primary and secondary data. This research uses qualitative and descriptive method.The result of this research show that BPD Kuok Village can’t doing its functions as the representative of the village in seeing, controling performance of head village. Head of village in performing their duties without any supervision by BPD Kuok Village. BPD can’t control as optimally. There are still many offense head village do. So can result in the accurence of irregularities that plagued the survival of the village comunitty Kuok.Keywords : Function, Control, The Conference Village